Organ donor registration in the UK: The need for informed consent for ante-mortem interventions to facilitate organ donation. (June 2019) - Brown, Sarah-Jane R.
A generic consent model for the organ donation process currently permeates organ donation policy in the United Kingdom. The National Health Service Blood and Transplant's (NHSBT's) strategy for increasing organ donation rates in the United Kingdom includes interpreting a person's registration on the Organ Donor Register (ODR) as justifying changes to the end-of-life care of the ODR registrant once incapacitated. However, individuals registering on the ODR are not currently provided with specific information regarding any ante-mortem procedures that may be carried out to facilitate organ donation. In this article, I argue that a specific consent model for ante-mortem donor optimisation procedures is needed not only to facilitate the achievement of the best interests of ODR registrants once incapacitated but also to fulfil NHSBT's obligations to ODR registrants under the law on informed consent. I argue that NHSBT owes a duty of care to ODR registrants and that the implications of this duty of care include incorporating informed consent standards into the process of ODR registration.